Social Media Platform: Osun State Government Communication on X Handle - Hamzat, Fatahi Owolabi; Adelakun , Lateef Adekunle; Ambassador-Birkins, Helen O.C (Kashere Journal of Politics and International Relations, 2024)
Often considered an informal means of communication and a playful medium solely occupied by the young and adventurous, social media has since made unprecedented and shocking inroads into the narratives of journalism and mainstream communication channels. Today, it is almost unthinkable to have a government without a running social media platform with which it is expected to engage the citizenry as against the traditional newspaper or radio stations owned by the government and used in pro-government information dissemination. This paper is predicated upon a need to examine the prevalence and effectiveness of social media as a government communication tool. Relying on the Agenda-Setting Theory and applying a blend of quantitative and qualitative analysis, it subjects ten randomly sampled X posts from the Osun state X handle between June to November, 2023 to content analysis. It found among other things that the X handle of Osun state government has a wide reach but a disproportionately low engagement statistics. More often than not, the critics of the government engage the posts more and the criticisms are often targeted at the handler and the personality of the governor. Yet, the paper concludes that the posts are effective at engendering communication between government and the people although the agenda is often defeated as the cordiality expected by the government is often thwarted while the issues often get thread jacked, criticized and thrashed. The paper suggests a more effective engagement in the form of responses to replies as well as a clearer feedback mechanism from the handle.